Fetal Alcohol Spectrum Disorder among Aboriginal children under six years of age and living off reserve - Werk, Christine; Cui, Xinjie; Tough, Suzanne (First Peoples Child & Family Review)

(untitled) (First Nations Child and Family Caring Society of Canada, 2013)
Fetal Alcohol Spectrum Disorders (FASD) are caused by consumption of alcohol during pregnancy and the prevalence of these disorders in Canada is not well established. Statistics Canada’s Aboriginal Children’s Survey (2006) was used in the current study to assess the prevalence of FASD among Aboriginal children living off reserve across Canada. Characteristics of Aboriginal children with or without a diagnosis of FASD and living in Western Canada were also assessed. Rates of FASD were higher in Alberta and Manitoba than other provinces and territories. For these children who were diagnosed with FASD half received treatment for FASD and treatment rates did not vary across provinces. In Western Canada, FASD was more common among children identified as First Nations, and among older children. Rates of FASD were also higher for Aboriginal children who lived in low income situations, who had experienced food insecurity, or who lived with foster parents. Therefore, Aboriginal children with FASD likely experience other life challenges and these factors should be considered when treating these young children.